DOES BMI AFFECT CHOLESTEROL, SUGAR, AND BLOOD PRESSURE IN GENERAL POPULATION? - Faheem, Mohammad; Qureshi, Saqib; Ali, Jabar; Hameed, Hameed; Zahoor, Zahoor; Abbas, Farhat; Gul, Adnan Mahmood; Hafizullah, Mohammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Higher BMI in child hood is also associated with an increase risk for coronary heart disease in adulthood. Impaired glucose tolerance is highly prevalent in children and adolescents with severe obesity. Positive correlations between BMI and glucose, lipids and BP have previously been reported. The objective of this study was to find the correlation of BMI with cholesterol and sugar level in general population. Methods: This study was a part of '˜Peshawar Heart Study', performed at Cardiology Department, Lady Reading Hospital, Peshawar in 2008-2009. Individuals with different ages, gender, professions, socioeconomic class were randomly selected from general population. Random blood sugar and cholesterol was measured with strip method. Height and weight of each individual was recorded and BMI calculated. All individuals were asked about any current medical illness and whether they were performing any exercise or not. Using SPSS-13, descriptive statistics were used for frequencies. Bivariate correlations were used for measuring correlation between BMI, sugar and cholesterol. Partial correlations were used to factor out the effect of other variables. Results: A total of 2,270 individuals, 1,798 (79.2%) male and 472 (20.8%) female were examined. Mean age was 38.47±12.66. Mean BMI was 26.38±4.97. Mean RBS was 113.7±47.145. Mean cholesterol was 168.47±28.23. Exercise was performed by 929 (40.90%) individuals. Diabetes was present in 113 (5.0%) and history of high cholesterol in 25 (1.1%) persons. When bivariate correlation analysis were done systolic BP, diastolic BP, RBS and cholesterol had positive correlation with BMI [correlation coefficient of 0.317 (p<0.000), 0.319(p<0.000), 0.125 (p<0.000) and 0.205 (p<0.000) respectively]. These variables also showed a positive correlation among themselves. After factoring out the effects of age, exercise, gender and current medical status on the above correlations, the correlation of RBS and cholesterol with BMI decreased to 0.025 (p=0.232) and 0.135 (p<0.000) respectively and between sugar and cholesterol decreased to 0.018 (p=0.401). Conclusion: In general population BMI is positively correlated with RBS and cholesterol. With the effect of age, sex, exercise and current medical status, this correlation is reduced. Keywords: Body Mass Index (BMI), RBS, Cholesterol, Obese, Obesity